2009
DOI: 10.1590/s1809-29502009000200006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da satisfação dos pacientes atendidos em uma clínica-escola de fisioterapia de Santo André, SP

Abstract: O objetivo deste estudo foi verificar o grau de satisfação com o atendimento fisioterapêutico de 51 pacientes (idade 47,6±14,8 anos) que estavam recebendo tal atendimento em uma clínica-escola que atende gratuitamente. O nível de satisfação foi avaliado por um questionário brasileiro, validado, sobre a satisfação dos pacientes com a fisioterapia. A ampla maioria (77%) dos pacientes eram de baixo nível socioeconômico. Os resultados mostram que os pacientes apresentam um alto nível de satisfação com o at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
0
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 11 publications
7
10
0
15
Order By: Relevance
“…In accordance with the studies by Suda et al 21 , Matias et al 20 and Gonçalves et al 22 , we found a high level of satisfaction in the studied sample. The result presented satisfaction in the studied sample.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with the studies by Suda et al 21 , Matias et al 20 and Gonçalves et al 22 , we found a high level of satisfaction in the studied sample. The result presented satisfaction in the studied sample.…”
Section: Discussionsupporting
confidence: 93%
“…In the study by Suda et al 21 , the research was conducted with users of a physical therapy school clinic and presented high level of general satisfaction. This study also presented high level of general satisfaction, even though it analyzed home care patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the income criterion alone was not correlated with the level of satisfaction. Therefore, we can conclude that a higher or lower income does not directly impact satisfaction 5,29 .…”
Section: Discussionmentioning
confidence: 84%
“…The questionnaires used in the study were developed based on questionnaires used in patient satisfaction studies (14) and usability studies (15). The socioeconomic questionnaire (SEQ) is composed of 13 subjective questions addressing sociodemographic aspects.…”
Section: Evaluation Toolsmentioning
confidence: 99%